The role of cultural identity in sustaining village-level conflict: Lessons from Pombewe, Indonesia - Adam, Adam (Edelweiss Applied Science and Technology, 2025)
This study explores the role of cultural identity in sustaining village-level conflicts in Pombewe, Indonesia, where historical grievances and communal loyalties shape inter-Dusun (inter-village) relations. Using qualitative research methods, including in-depth interviews and participant observation, the study finds that these conflicts are deeply embedded in cultural narratives and social identities, often intensified by concerns over honor and territorial claims. While socio-economic factors, such as resource competition, may act as catalysts, it is the cultural dimensions that sustain long-standing tensions, reinforcing cycles of hostility and mistrust. The findings highlight the need for culturally sensitive conflict resolution strategies that engage community leaders in fostering dialogue and reconciliation. However, as the research focuses on a single village, further studies across diverse rural settings in Indonesia are necessary to identify broader patterns and develop effective interventions. By addressing the cultural foundations of conflict, this study provides valuable insights for policymakers and community leaders working toward sustainable peace in conflict-prone regions.